Molecular structure of the human genome - Wolfe, Jonathan (Henry Stewart Talks, 2009)
The structure of the human genome, Chromosomes, Ideogram, How is DNA organized on a micro scale, CoT curves, Equilibrium density gradient centrifugation, Sequence content of the human genome, Genes